Pengaruh Reward & Punishment Dan Literasi Digital Terhadap Hasil Belajar Siswa Kelas X Fase E Pada Pembelajaran Ekonomi Di SMA Negeri 8 Padang - Jusmita Weriza; Widya Astuti; Annisa sabrina (Kilau Publishing, 2025)
This study aims to determine 1) the effect of Reward & Punishment on the learning outcomes of class X phase E students in economics learning at SMA 8 Padang, 2) the effect of digital literacy on the learning outcomes of class X phase E students in economics learning at SMA 8 Padang, and 3) the combined effect of Reward & Punishment and digital literacy on the learning outcomes of class X phase E students in economics learning at SMA 8 Padang. The method used is quantitative with a research population of 356 students. The sampling technique uses proportional random sampling, so that a sample of 188 students is obtained. The data collection technique was carried out through questionnaires and analyzed using multiple linear regression analysis with SPSS version 25, as well as hypothesis testing using the t test and F test. The results of the study showed that: 1) there is a significant influence between Reward & Punishment on learning outcomes with a calculated t value of 3.034> t table 1.972 and a sig value of 0.003 <0.05, 2) there is a significant influence between digital literacy on learning outcomes with a calculated t value of 2.878> t table 1.972 and a sig value of 0.004 <0.05, 3) there is a combined influence between Reward & Punishment and digital literacy on learning outcomes with a calculated F value of 11.735> F table 3.04 and a sig value of 0.000 <0.05. The conclusion of this study is that Reward & Punishment and digital literacy have a significant effect on the learning outcomes of class X phase E students in economics learning at SMA Negeri 8 Padang.